Extraction of soliton solutions for the fractional Kaup-Boussinesq system: A comparative study - Alsaud, H.; Raza, N.; Arshed, S.; Butt, A. Rashid; İnç, Mustafa (Soc Mexicana Fisica, 2024)
This paper is based on finding soliton solutions to fractional Kaup-Boussinesq (FKB) system. The fractional derivatives such as beta-derivative and truncated M-fractional derivative are used in this study. The unified approach, generalized projective riccati equations method (GPREM) and improved tan (phi(zeta)/2)-expansion approaches are efficiently used for obtaining bright soliton, dark soliton, singular soliton, periodic soliton, dark-singular combo soliton and dark-bright combo soliton. The numerical simulations are also carried out by 3D and 2D, graphs of some of the obtained solutions to discuss the fractional effects.
Keywords: Integrating schemes; unified method; GPREM; improved tan ( phi ( zeta ) / 2 )-expansion; beta-derivative; truncated M-fractional deriva- tive